ANTI-BACTERIAL ACTIVITY OF SILVER NANOPARTICLES SYNTHESIZED USING PHYLLANTHUS AMARUS AQUEOUS & ANDROGRAPHIS PANICULATA ETHANOLIC EXTRACTS - M. Ananda Chitra; S. Ramesh (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The use of metallic silver as an antimicrobial agent has been recognized for centuries. Silver nanoparticles (SNP) are now incorporated in apparel, wound dressings, appliances, cosmetics, paints and plastics for their antimicrobial properties. Generally, silver nanoparticles are prepared by a variety of chemical methods. In this study, we have used Phyllanthus amarus and Andrographis paniculata herbal plants leaves and stem extracts to synthesis SNP and were characterized by UV-Vis spectroscopy and Transmission Electron Microscopy (TEM). SNP capped with plant extracts gave absorption peak at 420 nm as expected for silver and broadening of peak were also noticed. TEM images suggested that they were of almost spherical shape and in the range of 7-60 nm in size. Antibacterial activity of plant extracts capped SNP were tested in Mueller-Hinton agar by well diffusion method against Staphylococcus aureus, Bacillus subtilis, Proteus vulgaris, Escherichia coli and Salmonella Typhimurium. SNP of 1 mg/ml and 5 mg/ml of P.amarus exhibited almost similar antibacterial activity, whereas, 5mg/ml, not 1 mg/ml of SNP capped with A. paniculata exerted antibacterial activity. The highest zone of inhibition was noticed against B.subtilis followed by S.aureus and P.vulgaris and the least zone of inhibition was observed against E.coli and S.Typhimurium. Green synthesis of SNP is cost effective and environment friendly. Further studies are required to explore the possibility of use of P.amarus capped silver nanoparticles for the treatment of burn and wound.